Functional performance of the upper limb and the most common boxing-related injuries in male boxers: a retrospective, observational, comparative study with non-boxing population - Giannatos, V.; Panagopoulos, A.; Antzoulas, P.; Giakoumakis, S. I.; Lakoumentas, J.; Kouzelis, A. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background To investigate the functional status and recording the most common injuries of the upper limb in male Greek boxing squad in comparison to the general population.